Electricity and manufacturing firm profits in Myanmar - Lisa Chauvet; Alvaro de Miguel Torres; Alexa Tiemann (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
We examine the impact of being located in areas with higher availability of electricity on manufacturing firm profits in Myanmar. Using a survey of 497 manufacturing firms conducted in 2014 and covering the whole territory of Myanmar, we investigate whether firms belonging to industries that tend to make more intensive use of electricity show better performance if such firms are located in areas with higher availability of electricity. We find that electricity provided by the national power grid tends to have a positive impact on manufacturing firm profits. Results are robust to reducing the sample to firms that could not have chosen their location endogenously, as well as to the use of an instrumental variable.
Keywords: H4; O13; O14; L60; 330